The integration of single-cell RNA sequencing and spatial transcriptomics reveals the tumor microenvironment and spatial organization of testicular diffuse large B-cell lymphomas - Xiaolong Wu; Jie Shi; Mujun Lu; Damin Yun; Sheng Gao; Longfei Hu; Fei Sun (Genes and Diseases)
Primary testicular diffuse large B-cell lymphomas (PT-DLBCL) are a collection of 1%–9% of testicular tumors. However, the characterization of the tumor microenvironment and spatial organization of PT-DLBCL is poorly understood. We profiled the transcriptomes of 19,559 single cells derived from a PT-DLBCL patient via single-cell RNA sequencing. We found that the tumor microenvironment was majorly composed of three exhausted CD8+ T cell subpopulations and two B cell subpopulations, and the genetic heterogeneity was further analyzed. Then, transcription factors related to PT-DLBCL cell proliferation and development were identified. Our results demonstrated that inhibiting E2F and CREB could decrease cell proliferation, induce apoptosis in human B-lymphoma cells, and inhibit tumor growth in xenograft testicular DLBCL models. Subsequently, chromatin immunoprecipitation sequencing was performed to identify the enriched loci of E2F and CREB that regulate human B-lymphoma cell proliferation and apoptosis. To annotate the precise spatial cellular composition of testicular DLBCL, we performed spatial transcriptomics. The spatial organization of PT-DLBCL, especially the spatial location of exhausted CD8+ T and B cells, was identified. Concurrently, we delineated the expression patterns of key genes, including MALAT1, RPS3A, RPS7, RPS23, RPS27A, IGHM, HINT1, and HSPA8, across various regions. In this study, we unveiled the spatial architecture of the tumor microenvironment in DLBCL, where exhausted T cells were strategically positioned around tumor B cells, and macrophages, in turn, encircled the exhausted T cells. Inhibition of E2F and CREB in the tumor microenvironment may be a novel therapeutic option for testicular DLBCL patients.